Pengembangan Sistem Informasi Pengelolaan Barang berbasis Website (Studi Kasus: Hikmah Jaya Plastik Jombang) - Harith Irawan; Denny Sagita Rusdianto; Mahardeka Tri Ananta (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Hikmah Jaya Plastik Jombang is a shop providing various plastics and cake ingredients located in Jombang Regency. The problem that employees often complain about is the inventory calculation process which takes about one hour every day before the store closes, Frequent calculation errors made by the shop cashier due to errors in writing or reading the total of items on the sales transaction notes also become the case in this process. In supervisor's term, there is also an error resulting from the validation of the existing goods, this can occur due to the possibility that the sales transaction note is lost before the stock calculation is carried out. Employee also finds difficulty in monitoring the amount of goods, and this prolongs the process of restocking. Based on these problems, a goods management information system was developed. System development is carried out using an object-oriented approach and using the SDLC waterfall. Research sequentially includes literature studies, requirements engineering, design, implementation, testing, conclusions and suggestions. The requirements engineering phase showed 42 functional requirements and 1 non-functional requirement. The design phase includes architectural design, component design and database design. The implementation phase is executed using the PHP programming language and the Laravel framework. The unit testing phase was carried out using the white box testing approach with 100% valid results. Validation testing was carried out using black box testing approach with 100% valid results. Compatibility testing was carried out on Google Chrome, Microsoft Edge and Mozilla Firefox browsers with 100% valid results.